PERENCANAAN PRODUKSI SIRUP BUAH PEPINO (SOLANUM MURICATUM) PADA INDUSTRI SKALA MIKRO - Aditya Nugroho; Susinggih Wijana; Nur Lailatul Rahmah (Industria: Jurnal Teknologi dan Manajemen Agroindustri, 2012)
Pepino fruit is a fruit that is included in the family solanaceae and can be developed as a base for the manufacture of syrup. The purpose of this study is to get the quality of pepino fruit syrup production on the scale and get production planning at the micro-scale industries. The research was done by the previous research scaling, ie pepino fruit syrups with the addition of carrageenan 0.4% (w / v), and be repeated twice. The results of chemical testing showed that a total of 69.15 brix syrup solids, viscosity of 1.53 cps, vitamin C of 3.02 mg / 100ml, and 66.4% total sugar. Physical tests using paired comparison test shows the results of the micro-scale industry is not different from the results of preliminary research. The need for utilities including water IDR 24743.00 / month, electricity is IDR 37,033.00 / month, and LPG at IDR 246,093.00 / month. Financial analysis includes determination of  HPP IDR 1240.94 / bottle, BEP achieved unit sales volume at 1689 units, and the payback period for 2 years and 3 months 18 days. Keywords: Fruit Pepino, Carragenan, Production Planning, Syrup Fruit Pepino, Micro Scale Industries